Strategi Promosi Digital pada Home Industry Kue Kering di Kabupaten Solok Selatan - Tiwi , Tiwi; Annas, Firdaus; Raini, Putri (Yayasan Lembaga Studi Makwa, 2023)
The rapid advancement of digital technology has significantly influenced business strategies, including in the field of Islamic economics. However, the integration of sharia principles with digital business practices poses unique challenges, such as maintaining compliance with Islamic values while embracing innovation and entrepreneurship. This study aims to address the issue of how Islamic economic institutions in Indonesia can effectively implement business strategy control, innovation, and entrepreneurship to thrive in the digital era. Using a qualitative-descriptive method, the research involved an in-depth analysis of data collected from Islamic financial institutions, entrepreneurs, and policymakers. The study identifies key strategies for aligning digital innovation with sharia principles, focusing on the roles of strategic control, technological innovation, and entrepreneurship as essential components. The findings reveal that Islamic economic institutions can enhance their competitiveness by adopting comprehensive strategy control mechanisms, fostering technological innovation in products and services, and encouraging entrepreneurship that upholds Islamic ethical values. The integration of these three elements not only ensures operational efficiency and compliance but also creates a sustainable and competitive sharia-based economic ecosystem. This research contributes to the literature by offering practical recommendations for strengthening collaboration between stakeholders, such as governments, academia, and industry players, to develop inclusive digital innovations within the framework of Islamic economics. By doing so, this study highlights the potential of Islamic economic principles to serve as a foundation for sustainable economic development in Indonesia in the digital era.